A study to identify bacteriological profile and other risk factors among diabetic and non-diabetic foot ulcer patients in a Guyanese hospital setting - Kurup, Rajini; Ansari, Abdullah Adil (Diabetes & metabolic syndrome clinical research & reviews, 2019)
Diabetic foot infection is a global epidemic and a major public health concern. Development of microbial resistance to many antimicrobial agents in foot ulcer leads to serious complications. Therefore, the study aims to identify the microbiological profile and the potential risk factors among diabetic and non-diabetic foot ulcer patients. A prospective cross sectional study was carried out among 183 ulcer patients from diabetic foot clinic and wound dressing clinic at the public health hospital, Guyana. A total of 254 bacteria were isolated from the study with an average of 1.4 organism per lesion. Gram negative bacteria (63.0%) were prevalent than gram positive bacteria (37.0%) in this study. Among DF patients, Pseudomonas aeruginosa (18.8%) was the most common isolate followed by Escherichia coli (13.9%) among gram negative group. Were as MRSA (12.1%) followed by MSSA (7.9%) dominated among gram positive group in diabetic foot patients. Almost 42.1% (95% CI 34.8–49.6) of the infections were caused by poly-microbial. Interestingly, a stepwise logistic regression model determined increasing age and lack of health education as independent risk factor identified for acquiring an MDR wound infection (OR = 1.1; p ≥ 0.05; 95% CI 1.0–1.1). Mild, moderate and severe infection among MDR and NMDR patients were recorded as 45.3% (95% CI 32.8–58.3), 26.5% (95% CI 16.3–39.1), 28.1% (95% CI 17.6–40.8) and 51.3% (95% CI 41.9–60.5), 32.8% (95% CI 24.4–42.0), 16.0% (95% CI 9.9–23.8). Therefore, it is concluded that there's an urgent need for surveillance of resistant bacteria in diabetic foot infections to reduce the risk of major complications.